Invasive Aspergillus infection of middle ear in a patient treated with secukinumab, methotrexate, and corticosteroids for psoriasis and psoriatic arthritis - Rob, Filip; Školoudík, Lukáš; Chrobok, Viktor; Dědková, Jana; Kašparová, Petra; Podrazilová, Lucie (The Journal of dermatological treatment, 2022)
Mucocutaneous mycotic infections are common complications in patients on IL-17 inhibitor therapy. We report a case of a 33-year-old male with severe psoriasis and psoriatic arthritis on secukinumab combined with methotrexate and prednisone with swelling, otorrhea, and pain of the right ear and external auditory canal. Due to progressive hypacusis, a surgical solution was chosen. Tissue samples taken during surgery revealed the presence of Aspergillus fumigatus. Aspergillosis should be suspected in prolonged otorrhea, especially in immunocompromised patients. Without intervention, the disease could be fatal.
Keywords: psoriatic arthritis; Humans; hormony kůry nadledvin; methotrexát; secukinumab; Psoriasis; Arthritis, Psoriatic; dospělí; Methotrexate; psoriáza; lidé; anti-IL-17; střední ucho; Adult; Aspergillosis; Male; psoriasis; Adrenal Cortex Hormones; mužské pohlaví; psoriatická artritida; Ear, Middle; aspergilóza